CURRENT PRODUCTION SAFETY PROBLEMS IN ENTERPRISES OF THE OIL AND GAS COMPLEX OF UKRAINE - KOZAK, Stanislav (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Production in the oil and gas sector, causing the existence of an increased risk of hazards both for the internal and external environment of operation, requires increased attention to the problems of ensuring industrial safety. The issue of ensuring the production safety of the enterprises of the oil and gas complex of Ukraine is particularly relevant in the context of the Russian-Ukrainian war, which has been ongoing since 2014 and is in full-scale phase for the second year in a row, accompanied by significant destruction throughout the country.The problems of improving the functioning of enterprises of the oil and gas complex of Ukraine are constantly in the field of view of researchers, each of whom focuses attention on a certain set of problems and possible ways to solve them. At the same time, more attention is paid to the problem of production safety of oil and gas enterprises from the point of view of its individual components. Thus, the modern domestic scientific discourse does not focus on the problems of production safety of the enterprises of the oil and gas complex, which actualizes the need for research on the specified issues.The purpose of the study is to substantiate the components of industrial safety of enterprises of the oil and gas complex of Ukraine and to determine the problems of its provision in the context of the Ukrainian-Russian war.Methods. The methodological basis of the research was made up of general scientific and special methods of economic science, in particular methods of theoretical generalization and logical abstraction. Analytical materials of the Ministry of Environmental Protection and Natural Resources of Ukraine, the State Labor Service of Ukraine, the State Statistics Service, the World Bank, the Government of Ukraine and the European Commission were used in the research process and processed using methods of statistical analysis: comparison, grouping, calculation of growth rates etc.The results. The essence of the categories "safety" and "industrial safety" of the enterprise was studied. Existing domestic and foreign approaches to identifying the key components of industrial safety of oil and gas complex enterprises are analyzed. The author's approach to the formation of the composition of industrial safety elements is proposed and the characteristics of each of them are given. The situation with industrial injuries in the industry in the pre-war period was studied and the losses of the sector and ecology as a result of hostilities were analyzed. The peculiarities of modern processes of ensuring industrial safety at the enterprises of the oil and gas complex of Ukraine are substantiated
Keywords: oil and gas complex; industrial safety; components of industrial safety; modern problems; oil and gas enterprises